Development of a Digital Module to Strengthen Multicultural Citizenship Competence in Higher Education - Mas Fierna Janvierna Lusie Putri; Sunarso Sunarso; Samsuri Samsuri; Sugiyanto Sugiyanto; Yatti Rosmiati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study presents the design and validation of a digital learning module aed at enhancing multicultural citizenship competence among higher education students. Using the Research and Development (R&D) method and the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation) the module was tested across three Indonesian universities: STKIP Kusuma Negara, STKIP Arrahmaniyah, and Pamulang University. A total of 30 students participated in preliminary testing, followed by 54 students in field trials. The module and its accompanying web-based digital were evaluated by two subject matter experts and two media specialists to ensure content accuracy and media quality. Results showed high feasibility ratings (module: 87.56%; web digital: 91.31%), strong effectiveness (module: 88.71%; web digital: 88.80%), and notable practicality (module: 86.61%; web digital: 90.30%). Feedback from lecturers and students emphasized the module’s accessibility, clear structure, interactive features, and adaptability to diverse learning contexts. The digital format allowed for flexible integration into various teaching environments, promoting student engagement and cross-cultural understanding. This research contributes an innovative, culturally responsive, and technology-enhanced resource for civic education, supporting the development of inclusive, tolerant, and globally aware citizens in higher education settings. It also demonstrates the potential of digital pedagogy in advancing multicultural values in Curricula.